PHARMACEUTICAL INNOVATIONS: AN OVERVIEW OF NIGELLA SATIVA ESSENTIAL OIL IN ORAL HEALTH MANAGEMENT - Amol R. Patil; Dr. Avish D. Maru; Masidd Khalate (The Bioscan, 2025)
Periodontal infections, such as gingivitis and periodontitis, are serious threats to oral health, frequently resulting in tooth loss if left untreated. These disorders are distinguished by inflammation, bacterial colonization, and tissue breakdown within the periodontium. Traditional therapies frequently use antibacterial drugs and scale processes, but new study investigates the possibilities of natural remedies, such as Nigella sativa (N. sativa), in controlling these disorders. Furthermore, N. sativa contains antioxidant and anti-inflammatory properties, which are important in reducing oxidative stress and inflammatory reactions associated with periodontal disorders. Furthermore, its antibacterial and antifungal characteristics make it a good candidate for treating oral infections. Finally, N. sativa emerges as a promising supplementary therapy for periodontal disease management, providing a natural and potentially beneficial alternative to conventional treatments. However, additional research, particularly clinical trials, is required to confirm its efficacy and safety in clinical practice. N. sativa, often known as black cumin, has a long history of therapeutic usage because to its several pharmacological qualities, which include anti-inflammatory, antioxidant, and antibacterial activities. Studies have yielded positive effects in terms of increasing gingival health and managing periodontal disorders. N. sativa extracts have shown antibacterial activity against common periodontal infections and have been investigated as local drug delivery agents in periodontal therapy. N. sativa essential oil, rich in medicinal chemicals like thymoquinone and carvacrol, was extracted through hydro-distillation and supercritical fluid extraction, and its chemical content was determined using analytical techniques. Furthermore, N. sativa has shown antioxidant and anti-inflammatory activities, which are crucial in mitigating the oxidative stress and inflammatory responses associated with periodontal diseases. Additionally, its antibacterial and antifungal properties make it a promising candidate for combating oral pathogens. In conclusion, N. sativa emerges as a potential adjunctive therapy for managing periodontal diseases, offering a natural and potentially effective alternative to conventional treatments. However, further research, particularly clinical trials, is warranted to validate its efficacy and safety in clinical practice.